Tinjauan Pustaka Perbandingan Efektivitas Metode Jigsaw Learning dan Numbered Heads Together terhadap Hasil Belajar Siswa - Miratul Munawwaroh; Septi Gumiandari (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The enhancement of student learning outcomes is a primary goal of various innovations in teaching methods. This study systematically reviews the effectiveness of cooperative learning methods, specifically Jigsaw Learning and Numbered Heads Together (NHT), in improving student learning outcomes. Using a systematic literature review approach, the research analyzes twelve studies published between 2019 and 2025 that compare these two methods. The findings indicate that both Jigsaw Learning and NHT possess unique strengths; Jigsaw Learning fosters deep understanding through collaborative expertise, while NHT promotes active participation through structured discussions. Despite some studies showing no significant differences in effectiveness, others highlight context-dependent advantages of each method. The implications suggest that educators should consider the specific learning objectives and student characteristics when selecting or combining these methods to optimize educational outcomes.